A common energy market in the Eurasian Economic Union: Implications for the European Union and energy relations with Russia - Maria Pastukhova; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2016)
To the east of the European Union a regional energy market is taking shape under the auspices of the Eurasian Economic Union (EEU). Even if the interests of the participating states diverge and the ultimate shape of the market remains unclear, the development is likely to be substantial. On the one hand, it threatens to deepen the fragmentation of energy markets in Europe and Asia, on the other the process could generate new opportunities for cooperation and larger spheres of integration. It is thus worth exploring at this early stage the extent to which the emerging energy market is compatible with the European Union and the European Energy Community. It is especially important to track the effects in the common neighbourhood, above all Ukraine, in order to avoid renewed geopolitical disruption. (SWP Comments)
Keywords: 320